Orexins activates protein kinase C-mediated Ca2+ signaling in isolated rat primary sensory neurons - Ozcan, M.; Ayar, A.; Serhatlioglu, I.; Alcin, E.; Sahin, Z.; Kelestimur, H. (My University, 2010)
Previous results have suggested that orexins causes a rise of intracellular free calcium ([Ca2+]i) in cultured rat dorsal root ganglion (DRG) neurons, implicating a role in nociception, but the underlying mechanism is unknown. Hence, the aim of the present study was to investigate whether the orexins-mediated signaling involves the PKC pathways in these sensory neurons. Cultured DRG neurons were loaded with 1 ?mol Fura-2 AM and [Ca2+]i responses were quantified by the changes in 340/380 ratio using fluorescence imaging system. The orexin-1 receptor antagonist SB-334867-A (1 ?M) inhibited the calcium responses to orexin-A and orexin-B (59.1±5.1 % vs. 200 nM orexin-A, n=8, and 67±3.8 % vs. 200 nM orexin-B, n=12, respectively). The PKC inhibitor chelerythrine (10 and 100 ?M) significantly decreased the orexin-A (200 nM)-induced [Ca2+]i increase (59.4±4.8 % P<0.01, n=10 and 4.9±1.6 %, P<0.01, n=9) versus response to orexin-A). It was also found that chelerythrine dose-dependently inhibited the [Ca2+]i response to 200 nM orexin-B. In conclusion, our results suggest that orexins activate intracellular calcium signaling in cultured rat sensory neurons through PKC-dependent pathway, which may have important implications for nociceptive modulation and pain. © 2010 Institute of Physiology v.v.i., Academy of Sciences of the Czech Republic, Prague, Czech Republic.
Keywords: Calcium signaling; Nociception; Orexin A; Protein kinase C; Sensory neuron